The effect on the gastrointestinal tract of various forms of alendronate in comorbid patients taking NSAIDs - I. A. Shafieva; S. V. Bulgakova; A. V. Shafieva; N. A. Kniazev (Медицинский совет, 2021)
Introduction. The use of bisphosphonates is associated with some risk of side effects. Gastrointestinal tract complications are particularly important in clinical practice, as they constitute the main reason for refusing bisphosphonate therapy.Objective: To evaluate the effect of various forms of alendronate on the gastrointestinal tract in comorbid patients taking NSAIDs.Materials and methods. The study included 88 women aged 58–65 years (mean age 61.5 ± 3.5 years) with polyosteoarthrosis combined with postmenopausal osteoporosis, who received NSAIDs at medium therapeutic doses to manage a pain syndrome for a long time (3–5 years). The patients were divided into two groups: a group of patients receiving alendronate in the form of a buffered solution (n = 45), and a group of patients receiving alendronate in the form of non-dissolving tablets (n = 43). The first group used Binosto (adendronic acid) 70 mg as effervescent tablets once a week. The results were assessed before initiation of treatment and 6 months after treatment with bisphosphonates. Symptoms were evaluated using the GerdQ questionnaire. Esophageal mucosal injury and gastroduodenal ulceration were assessed by upper gastrointestinal endoscopy.Results and discussion. After 6-month treatment, comparison of the two groups showed that the percentage of patients with a total GerdQ score of ≥ 8 points was significantly higher in the group of patients taking alendronate in the form of non-dissolving tablets (p = 0.04). The endoscopic findings showed that the number of patients with grade A reflux esophagitis in group 1 increased by 3.3%. The number of grade A reflux esophagitis cases in group 2 increased by 2.2%, those of grade B, C and D cases by 2.4%. The number of gastroduodenal ulcer cases also increased by 2.2% and 4.7% in groups 1 and 2, respectively. The number of gastroduodenal erosions increased by 3.5% in group 1 and 7% in group 2.Сonclusion. Symptoms were less severe in patients receiving alendronate in the form of a solution, which points to the importance of choosing the optimal oral bisphosphonate for each patient.